Free theorem for `forall z. (A,z) -> (B,z)`?

Suppose `g :: forall z. (A,z) -> (B,z)`. Is it necessarily the case that `g = first f` for some `f :: A -> B` (where `first f (a,b) = (f a, b)`), perhaps as a free theorem for the type of `g`? Note that `(A,)` and `(B,)` are functors and that `g` is a natural transformation, so `g . fmap h == fmap h . g` for any `h :: u -> v`. Equivalently, `g . second h == second h . g` (where `second h (a,b) = (a, h b)`). Thanks, -- Conal

Hi Conal, Am Sonntag, den 22.07.2018, 21:29 -0700 schrieb Conal Elliott:
Suppose `g :: forall z. (A,z) -> (B,z)`. Is it necessarily the case that `g = first f` for some `f :: A -> B` (where `first f (a,b) = (f a, b)`), perhaps as a free theorem for the type of `g`?
there used to be a free theorem calculator at http://www-ps.iai.uni-bonn.de/ft but it seems to be down :-( There is a shell client, ftshell, lets see what it says… it does not build with ghc-8.0 any more :-( Ah, but lambdabot understands @free: <nomeata> @free g :: forall z. (A,z) -> (B,z) <lambdabot> $map_Pair $id f . g = g . $map_Pair $id f Which is basically what you are writing here:
Note that `(A,)` and `(B,)` are functors and that `g` is a natural transformation, so `g . fmap h == fmap h . g` for any `h :: u -> v`. Equivalently, `g . second h == second h . g` (where `second h (a,b) = (a, h b)`).
Doesn’t that already answer the question? Let’s try to make it more rigorous. I define f :: A -> B f a = fst (g (a, ()) and now want to prove that g = first f, using the free theorem… which is tricky, because the free theorem is actually not as strong as it could be; it should actually be phrased in terms of relations relation, which might help with the proof. So let me try to calculate the free theorem by hand, following https://www.well-typed.com/blog/2015/05/parametricity/ g is related to itself by the relation [forall z. (A,z) -> (B,z)] and we can calculate g [forall z. (A,z) -> (B,z)] g ↔ ∀ z z' Rz, g [(A,z) -> (B,z)] g -- Rz relates z and z' ↔ ∀ z z' Rz, ∀ p p', p [(A,z)] p' → g p [(B,z)] g p' ↔ ∀ z z' Rz, ∀ p p', fst p = fst p' ∧ snd p Rz snd p' → fst (g p) = fst (g p') ∧ snd (g p) Rz snd (g p') ↔ ∀ z z' Rz, ∀ a x x', x Rz x' → fst (g (a,x)) = fst (g (a,x')) ∧ snd (g (a,x)) Rz snd (g (a,x')) We can use this to show ∀ (a,x :: z). fst (g (a,x)) = f a using (this is the tricky part that requires thinking) z := z, z' := (), Rz := λ_ _ -> True, a := a, x := x, x' := () as then the theorem implies fst (g (a,x)) = fst (g (a, ()) = f a. We can also use it to show ∀ (a,x :: z). snd (g (a,x)) = x using z := z, z' := z, Rz := const (= x), a := a, x := x, x' := x as then the theorem implies, under the true assumption x Rz z' (snd (g (a,x))) Rz (snd (g (a,x'))) ↔ snd (g (a,x)) = x And from ∀ (a,x :: z). fst (g (a,x)) = f a ∀ (a,x :: z). snd (g (a,x)) = x we can conclude that g = first f as intended. Cheers, Joachim -- Joachim Breitner mail@joachim-breitner.de http://www.joachim-breitner.de/

Thank you, Joachim! I'm refreshing my memory of free theorem construction
from that blog post. Regards, -- Conal
On Mon, Jul 23, 2018 at 8:33 AM, Joachim Breitner
Hi Conal,
Am Sonntag, den 22.07.2018, 21:29 -0700 schrieb Conal Elliott:
Suppose `g :: forall z. (A,z) -> (B,z)`. Is it necessarily the case that `g = first f` for some `f :: A -> B` (where `first f (a,b) = (f a, b)`), perhaps as a free theorem for the type of `g`?
there used to be a free theorem calculator at http://www-ps.iai.uni-bonn.de/ft but it seems to be down :-(
There is a shell client, ftshell, lets see what it says… it does not build with ghc-8.0 any more :-(
Ah, but lambdabot understands @free:
<nomeata> @free g :: forall z. (A,z) -> (B,z) <lambdabot> $map_Pair $id f . g = g . $map_Pair $id f
Which is basically what you are writing here:
Note that `(A,)` and `(B,)` are functors and that `g` is a natural transformation, so `g . fmap h == fmap h . g` for any `h :: u -> v`. Equivalently, `g . second h == second h . g` (where `second h (a,b) = (a, h b)`).
Doesn’t that already answer the question? Let’s try to make it more rigorous. I define
f :: A -> B f a = fst (g (a, ())
and now want to prove that g = first f, using the free theorem… which is tricky, because the free theorem is actually not as strong as it could be; it should actually be phrased in terms of relations relation, which might help with the proof.
So let me try to calculate the free theorem by hand, following https://www.well-typed.com/blog/2015/05/parametricity/
g is related to itself by the relation
[forall z. (A,z) -> (B,z)]
and we can calculate
g [forall z. (A,z) -> (B,z)] g ↔ ∀ z z' Rz, g [(A,z) -> (B,z)] g -- Rz relates z and z' ↔ ∀ z z' Rz, ∀ p p', p [(A,z)] p' → g p [(B,z)] g p' ↔ ∀ z z' Rz, ∀ p p', fst p = fst p' ∧ snd p Rz snd p' → fst (g p) = fst (g p') ∧ snd (g p) Rz snd (g p') ↔ ∀ z z' Rz, ∀ a x x', x Rz x' → fst (g (a,x)) = fst (g (a,x')) ∧ snd (g (a,x)) Rz snd (g (a,x'))
We can use this to show
∀ (a,x :: z). fst (g (a,x)) = f a
using (this is the tricky part that requires thinking)
z := z, z' := (), Rz := λ_ _ -> True, a := a, x := x, x' := ()
as then the theorem implies
fst (g (a,x)) = fst (g (a, ()) = f a.
We can also use it to show
∀ (a,x :: z). snd (g (a,x)) = x
using
z := z, z' := z, Rz := const (= x), a := a, x := x, x' := x
as then the theorem implies, under the true assumption x Rz z'
(snd (g (a,x))) Rz (snd (g (a,x'))) ↔ snd (g (a,x)) = x
And from
∀ (a,x :: z). fst (g (a,x)) = f a ∀ (a,x :: z). snd (g (a,x)) = x
we can conclude that
g = first f
as intended.
Cheers, Joachim
-- Joachim Breitner mail@joachim-breitner.de http://www.joachim-breitner.de/

Hi, I felt inspired to revive the free theorem calculator and gave it a new home (and a modern, browser-only, FRP-based implementation): http://free-theorems.nomeata.de/ which prints forall t1,t2 in TYPES, R in REL(t1,t2). forall (x, y) in lift{(,)}(id,R). (g_{t1} x, g_{t2} y) in lift{(,)}(id,R) as the free theorem, which is (if one squints) the same as my ∀ z z' Rz, ∀ a x x', x Rz x' → fst (g (a,x)) = fst (g (a,x')) ∧ snd (g (a,x)) Rz snd (g (a,x')) Enjoy, Joachim Am Montag, den 23.07.2018, 10:56 -0700 schrieb Conal Elliott:
Thank you, Joachim! I'm refreshing my memory of free theorem construction from that blog post. Regards, -- Conal
On Mon, Jul 23, 2018 at 8:33 AM, Joachim Breitner
wrote: Hi Conal,
Am Sonntag, den 22.07.2018, 21:29 -0700 schrieb Conal Elliott:
Suppose `g :: forall z. (A,z) -> (B,z)`. Is it necessarily the case that `g = first f` for some `f :: A -> B` (where `first f (a,b) = (f a, b)`), perhaps as a free theorem for the type of `g`?
there used to be a free theorem calculator at http://www-ps.iai.uni-bonn.de/ft but it seems to be down :-(
There is a shell client, ftshell, lets see what it says… it does not build with ghc-8.0 any more :-(
Ah, but lambdabot understands @free:
<nomeata> @free g :: forall z. (A,z) -> (B,z) <lambdabot> $map_Pair $id f . g = g . $map_Pair $id f
Which is basically what you are writing here:
Note that `(A,)` and `(B,)` are functors and that `g` is a natural transformation, so `g . fmap h == fmap h . g` for any `h :: u -> v`. Equivalently, `g . second h == second h . g` (where `second h (a,b) = (a, h b)`).
Doesn’t that already answer the question? Let’s try to make it more rigorous. I define
f :: A -> B f a = fst (g (a, ())
and now want to prove that g = first f, using the free theorem… which is tricky, because the free theorem is actually not as strong as it could be; it should actually be phrased in terms of relations relation, which might help with the proof.
So let me try to calculate the free theorem by hand, following https://www.well-typed.com/blog/2015/05/parametricity/
g is related to itself by the relation
[forall z. (A,z) -> (B,z)]
and we can calculate
g [forall z. (A,z) -> (B,z)] g ↔ ∀ z z' Rz, g [(A,z) -> (B,z)] g -- Rz relates z and z' ↔ ∀ z z' Rz, ∀ p p', p [(A,z)] p' → g p [(B,z)] g p' ↔ ∀ z z' Rz, ∀ p p', fst p = fst p' ∧ snd p Rz snd p' → fst (g p) = fst (g p') ∧ snd (g p) Rz snd (g p') ↔ ∀ z z' Rz, ∀ a x x', x Rz x' → fst (g (a,x)) = fst (g (a,x')) ∧ snd (g (a,x)) Rz snd (g (a,x'))
We can use this to show
∀ (a,x :: z). fst (g (a,x)) = f a
using (this is the tricky part that requires thinking)
z := z, z' := (), Rz := λ_ _ -> True, a := a, x := x, x' := ()
as then the theorem implies
fst (g (a,x)) = fst (g (a, ()) = f a.
We can also use it to show
∀ (a,x :: z). snd (g (a,x)) = x
using
z := z, z' := z, Rz := const (= x), a := a, x := x, x' := x
as then the theorem implies, under the true assumption x Rz z'
(snd (g (a,x))) Rz (snd (g (a,x'))) ↔ snd (g (a,x)) = x
And from
∀ (a,x :: z). fst (g (a,x)) = f a ∀ (a,x :: z). snd (g (a,x)) = x
we can conclude that
g = first f
as intended.
Cheers, Joachim
_______________________________________________ Haskell-Cafe mailing list To (un)subscribe, modify options or view archives go to: http://mail.haskell.org/cgi-bin/mailman/listinfo/haskell-cafe Only members subscribed via the mailman list are allowed to post. -- Joachim Breitner mail@joachim-breitner.de http://www.joachim-breitner.de/

"JB" == Joachim Breitner
writes:
JB> I felt inspired to revive the free theorem calculator and gave it a new JB> home (and a modern, browser-only, FRP-based implementation): Thank you, Joachim! I've used that calculator often, and was sad to see it shut down. -- John Wiegley GPG fingerprint = 4710 CF98 AF9B 327B B80F http://newartisans.com 60E1 46C4 BD1A 7AC1 4BA2

Thank you! Are you going to add a place for auxiliary definitions? Perhaps
also a few default definitions like lambdabot uses? As it is, there doesn't
seem to be a way to use non-Prelude to constructors. One more thing, that
was missing from the original: a good explanation of what the output means.
"lift" is particularly mysterious. Lambdabot seems to replace these with
calls to normal Haskell functions. Perhaps that can be done sometimes? One
last thing: the FRP interface seems a bit *too* responsive. It's not fun to
see error messages flashing on and off as I type. Perhaps it would make
sense to add a delay before activating one of those?
On Tue, Jul 24, 2018, 1:38 PM Joachim Breitner
Hi,
I felt inspired to revive the free theorem calculator and gave it a new home (and a modern, browser-only, FRP-based implementation):
http://free-theorems.nomeata.de/
which prints
forall t1,t2 in TYPES, R in REL(t1,t2). forall (x, y) in lift{(,)}(id,R). (g_{t1} x, g_{t2} y) in lift{(,)}(id,R)
as the free theorem, which is (if one squints) the same as my
∀ z z' Rz, ∀ a x x', x Rz x' → fst (g (a,x)) = fst (g (a,x')) ∧ snd (g (a,x)) Rz snd (g (a,x'))
Enjoy, Joachim
Am Montag, den 23.07.2018, 10:56 -0700 schrieb Conal Elliott:
Thank you, Joachim! I'm refreshing my memory of free theorem construction from that blog post. Regards, -- Conal
On Mon, Jul 23, 2018 at 8:33 AM, Joachim Breitner < mail@joachim-breitner.de> wrote:
Hi Conal,
Am Sonntag, den 22.07.2018, 21:29 -0700 schrieb Conal Elliott:
Suppose `g :: forall z. (A,z) -> (B,z)`. Is it necessarily the case that `g = first f` for some `f :: A -> B` (where `first f (a,b) = (f a, b)`), perhaps as a free theorem for the type of `g`?
there used to be a free theorem calculator at http://www-ps.iai.uni-bonn.de/ft but it seems to be down :-(
There is a shell client, ftshell, lets see what it says… it does not build with ghc-8.0 any more :-(
Ah, but lambdabot understands @free:
<nomeata> @free g :: forall z. (A,z) -> (B,z) <lambdabot> $map_Pair $id f . g = g . $map_Pair $id f
Which is basically what you are writing here:
Note that `(A,)` and `(B,)` are functors and that `g` is a natural transformation, so `g . fmap h == fmap h . g` for any `h :: u -> v`. Equivalently, `g . second h == second h . g` (where `second h (a,b) = (a, h b)`).
Doesn’t that already answer the question? Let’s try to make it more rigorous. I define
f :: A -> B f a = fst (g (a, ())
and now want to prove that g = first f, using the free theorem… which is tricky, because the free theorem is actually not as strong as it could be; it should actually be phrased in terms of relations relation, which might help with the proof.
So let me try to calculate the free theorem by hand, following https://www.well-typed.com/blog/2015/05/parametricity/
g is related to itself by the relation
[forall z. (A,z) -> (B,z)]
and we can calculate
g [forall z. (A,z) -> (B,z)] g ↔ ∀ z z' Rz, g [(A,z) -> (B,z)] g -- Rz relates z and z' ↔ ∀ z z' Rz, ∀ p p', p [(A,z)] p' → g p [(B,z)] g p' ↔ ∀ z z' Rz, ∀ p p', fst p = fst p' ∧ snd p Rz snd p' → fst (g p) = fst (g p') ∧ snd (g p) Rz snd (g p') ↔ ∀ z z' Rz, ∀ a x x', x Rz x' → fst (g (a,x)) = fst (g (a,x')) ∧ snd (g (a,x)) Rz snd (g (a,x'))
We can use this to show
∀ (a,x :: z). fst (g (a,x)) = f a
using (this is the tricky part that requires thinking)
z := z, z' := (), Rz := λ_ _ -> True, a := a, x := x, x' := ()
as then the theorem implies
fst (g (a,x)) = fst (g (a, ()) = f a.
We can also use it to show
∀ (a,x :: z). snd (g (a,x)) = x
using
z := z, z' := z, Rz := const (= x), a := a, x := x, x' := x
as then the theorem implies, under the true assumption x Rz z'
(snd (g (a,x))) Rz (snd (g (a,x'))) ↔ snd (g (a,x)) = x
And from
∀ (a,x :: z). fst (g (a,x)) = f a ∀ (a,x :: z). snd (g (a,x)) = x
we can conclude that
g = first f
as intended.
Cheers, Joachim
_______________________________________________ Haskell-Cafe mailing list To (un)subscribe, modify options or view archives go to: http://mail.haskell.org/cgi-bin/mailman/listinfo/haskell-cafe Only members subscribed via the mailman list are allowed to post. -- Joachim Breitner mail@joachim-breitner.de http://www.joachim-breitner.de/
Haskell-Cafe mailing list To (un)subscribe, modify options or view archives go to: http://mail.haskell.org/cgi-bin/mailman/listinfo/haskell-cafe Only members subscribed via the mailman list are allowed to post.

Hi, Am Dienstag, den 24.07.2018, 14:22 -0400 schrieb David Feuer:
Thank you! Are you going to add a place for auxiliary definitions?
You wish is my command: https://github.com/nomeata/free-theorems-static-webui/commit/eb8e820 Should be online in 10mins or so.
Perhaps also a few default definitions like lambdabot uses?
What do you mean? It has this background theory: https://github.com/nomeata/free-theorems-static-webui/blob/master/src/KnownD... (copied from free-theorems-webui)
As it is, there doesn't seem to be a way to use non-Prelude to constructors.
That is fixed now, is it?
One more thing, that was missing from the original: a good explanation of what the output means. "lift" is particularly mysterious. Lambdabot seems to replace these with calls to normal Haskell functions. Perhaps that can be done sometimes?
Pull requests welcome :-)
One last thing: the FRP interface seems a bit *too* responsive. It's not fun to see error messages flashing on and off as I type. Perhaps it would make sense to add a delay before activating one of those?
I guess I can use https://hackage.haskell.org/package/reflex-dom-0.3/candidate/docs/Reflex-Dom... for this somehow. But I guess I only want to delay errors, not successes – I will give it a shot. Cheers, Joachim -- Joachim Breitner mail@joachim-breitner.de http://www.joachim-breitner.de/

Hi, Am Dienstag, den 24.07.2018, 14:47 -0400 schrieb Joachim Breitner:
I guess I can use https://hackage.haskell.org/package/reflex-dom-0.3/candidate/docs/Reflex-Dom... for this somehow. But I guess I only want to delay errors, not successes – I will give it a shot
Sure, why not: https://github.com/nomeata/free-theorems-static-webui/commit/20c9aca it seems to work. If some reflex-expert could check if this makes sense, that would be great: -- | Errors are delayed, but successes go through immediatelly delayError :: (PerformEvent t m, MonadHold t m, TriggerEvent t m, MonadIO (Performable m)) => Dynamic t (Either a b) -> m (Dynamic t (Either a b)) delayError d = do delayedEvents <- delay 0.5 (updated d) d' <- holdDyn Nothing (Just <$> delayedEvents) return $ do now <- d past <- d' return $ case (past, now) of (Nothing, _) -> now -- before any delayed events arrive (_, Right _ ) -> now -- current value is good (Just x, Left _) -> x -- current value is bad, delay Cheers, Joachim -- Joachim Breitner mail@joachim-breitner.de http://www.joachim-breitner.de/

Personally, I'm old-fashioned. I don't mind having to press a button to
make it go. But my preferences are obviously not the end of the discussion.
On Tue, Jul 24, 2018, 3:15 PM Joachim Breitner
Hi,
Am Dienstag, den 24.07.2018, 14:47 -0400 schrieb Joachim Breitner:
I guess I can use
https://hackage.haskell.org/package/reflex-dom-0.3/candidate/docs/Reflex-Dom...
for this somehow. But I guess I only want to delay errors, not successes – I will give it a shot
Sure, why not: https://github.com/nomeata/free-theorems-static-webui/commit/20c9aca
it seems to work. If some reflex-expert could check if this makes sense, that would be great:
-- | Errors are delayed, but successes go through immediatelly delayError :: (PerformEvent t m, MonadHold t m, TriggerEvent t m, MonadIO (Performable m)) => Dynamic t (Either a b) -> m (Dynamic t (Either a b)) delayError d = do delayedEvents <- delay 0.5 (updated d) d' <- holdDyn Nothing (Just <$> delayedEvents) return $ do now <- d past <- d' return $ case (past, now) of (Nothing, _) -> now -- before any delayed events arrive (_, Right _ ) -> now -- current value is good (Just x, Left _) -> x -- current value is bad, delay
Cheers, Joachim
-- Joachim Breitner mail@joachim-breitner.de http://www.joachim-breitner.de/ _______________________________________________ Haskell-Cafe mailing list To (un)subscribe, modify options or view archives go to: http://mail.haskell.org/cgi-bin/mailman/listinfo/haskell-cafe Only members subscribed via the mailman list are allowed to post.
participants (4)
-
Conal Elliott
-
David Feuer
-
Joachim Breitner
-
John Wiegley